Determination of Tacrolimus Concentration and Protein Expression of P-glycoprotein in Single Human Renal Core Biopsies. (July 2018) - Krogstad, Veronica; Vethe, Nils Tore; Robertsen, Ida; Hasvold, Grete; Ose, Anne-Marthe Due; Hermann, Monica; Andersen, Anders Mikal; Chan, Joe; Skauby, Morten; Svensson, My Hanna Sofia; Åsberg, Anders; Christensen, Hege
Abstract : Introduction: Tacrolimus is currently the cornerstone of immunosuppressive protocols for renal transplant recipients. Despite therapeutic whole blood monitoring, tacrolimus is associated with nephrotoxicity and it has been hypothesized that intrarenal accumulation of tacrolimus and/or its metabolites is involved. As tacrolimus is a substrate of P-glycoprotein (P-gp), the expression and activity of this efflux transporter may influence the levels of tacrolimus in renal tissue. The aim was to develop and validate a method for simultaneous quantification of tacrolimus and demethylated metabolite concentrations as well as P-gp protein expression in tissue homogenates from single human renal core biopsies. Materials and Methods: Human renal tissue, with or without clinical tacrolimus exposure, was used for method development and validation. Homogenates were prepared by bead-beating, and concentrations of tacrolimus and its demethylated metabolites were analysed with liquid chromatography tandem mass spectrometry after protein precipitation. A Western blot method was used for semi-quantification of P-gp expression in the homogenates. The final methods were applied to renal core biopsies from two kidney recipients. Results and Discussion: The tacrolimus assay showed within- and between-run mean accuracy of 99.7 % to 107 % and coefficients of variation ⩽ 6.7 %. Matrix effects were non-significant and samples were stable for at least 3 months pre-analytically when stored at -80°C. Tacrolimus concentrations in two renal core biopsies were 62.6 and 43.7 pg/mg tissue, respectively. The methods for measurement of desmethyl-tacrolimus and P-gp expression were suitable for semi-quantification in homogenates from renal core biopsies. Conclusion: These methods may be valuable for elucidating mechanisms behind tacrolimus-induced nephrotoxicity in renal transplant recipients with respect to the possible involvement of intrarenal accumulation of tacrolimus and its metabolites.